Universal doping evolution of the superconducting gap anisotropy in single crystals of electron-doped Ba(Fe1−xRhx)2As2 from London penetration depth measurements. (8th May 2018) - Kim, Hyunsoo; Tanatar, M A; Martin, C; Blomberg, E C; Ni, Ni; Bud'ko, S L; Canfield, P C; Prozorov, R
Abstract: Doping evolution of the superconducting gap anisotropy was studied in single crystals of 4 d -electron doped Ba(Fe1− x Rh x )2 As2 using tunnel diode resonator measurements of the temperature variation of the London penetration depth . Single crystals with doping levels representative of an underdoped regime x   =  0.039 ( K), close to optimal doping x   =  0.057 ( K) and overdoped x   =  0.079 ( K) and x   =  0.131( K) were studied. Superconducting energy gap anisotropy was characterized by the exponent, n, by fitting the data to the power-law, . The exponent n varies non-monotonically with x, increasing to a maximum n   =  2.5 for x   =  0.079 and rapidly decreasing towards overdoped compositions to 1.6 for x   =  0.131. This behavior is qualitatively similar to the doping evolution of the superconducting gap anisotropy in other iron pnictides, including hole-doped (Ba, K)Fe2 As2 and 3 d -electron-doped Ba(Fe, Co)2 As2 superconductors, finding a full gap near optimal doping and strong anisotropy toward the ends of the superconducting dome in the T - x phase diagram. The normalized superfluid density in an optimally Rh-doped sample is almost identical to the temperature-dependence in the optimally doped Ba(Fe, Co)2 As2 samples. Our study supports the universal superconducting gap variation with doping and pairing at least in iron based superconductors of the BaFe2 As2 family.